The genus Potamogeton (Potamogetonaceae) in Mexico - González Gutiérrez, Martha (Instituto de Ecología, A.C., 1989)
Nine species of Potamogeton are recognized for Mexico against 28 names recorded from the literature. Potamogeton pectinatus L., P. crispus L., P. foliosus Raf. var. foliosus, P. pusillus L. var. pusillus, P. diversifolius Raf., P. nodosus Poiret, P. natans L., P. illinoensis Morong and P. praelongus Wulfen are described on the basis of their regional variation. Synonyms, distribution maps, reference to examined specimens, illustrations of diagnostic characters, key to species, and index to scientific names are herein included.